Individual and organisational factors of workplace bullying among junior doctors in Malaysia / Ely Zarina Samsudin - Ely Zarina, Samsudin (2019)
Introduction: Junior doctors’ experience of workplace bullying may affect their training and hamper the delivery of quality healthcare, yet no evidence on the prevalence and factors associated with workplace bullying among Southeast Asian junior doctors currently exist. Objectives: The aim of this study is five-fold. Firstly, it aims to systematically assess the prevalence, factors and outcomes of workplace bullying among junior doctors. Secondly, it intends to validate the psychometric properties of study instruments. Thirdly and fourthly, it aims to determine the association of individual traits and organisational characteristics with workplace bullying among junior doctors. Finally, it aims to produce a policy brief outlining policy recommendations based on associated factors. Materials and Methods: A systematic review was performed. A multicentre crosssectional study was then conducted in twelve government hospitals located within central zone of Malaysia, sampling a total of 1,074 junior doctors. A self-administered questionnaire comprising of several instruments was used to examine workplace bullying and associated factors. Post-hoc validation of instruments was performed using polychoric factor analysis with varimax rotation and assessing intraclass correlation coefficient and Cronbach’s alpha. The associations of factors of workplace bullying were modeled using mixed effects logistic regression. An objective policy brief was then prepared. v Results: Post-hoc validation suggested that study instruments were psychometrically sound. The overall six-month prevalence of workplace bullying among included junior doctors was 13%. After adjusting for potential confounders, individual traits such as moderate (AOR 4.40, 95% CI 2.20-8.77) and high (AOR 13.69, 95% CI 6.46-29.02) degree of negative affect, and high degree of neuroticism (AOR 2.99, 95% CI 1.71- 5.21), as well as organisational characteristics such as neutral (AOR 0.35, 95% CI 0.20- 0.62) and positive (AOR 0.33, 95% CI 0.11-0.98) organisational climate, moderate (AOR 0.39, 95% CI 0.25-0.59) and high (AOR 0.33, 95% CI 0.17-0.63) degree of clan culture, moderate (AOR 0.36, 95% CI 0.23-0.57) and high (AOR 0.42, 95% CI 0.24- 0.74) degree of adhocracy culture, moderate degree of hierarchy culture (AOR 0.64, 95% CI 0.41-0.98), moderate degree of production and achievement-oriented leadership style (AOR 0.36, 95% CI 0.17-0.76), moderate (AOR 0.49, 95% CI 0.30-0.80) and high (AOR 0.12, 95% CI 0.03-0.42) degree of organisational support, moderate degree of procedural justice (AOR 0.56, 95% CI 0.35-0.88), moderate (AOR 0.27, 95% CI 0.17- 0.42) and high (AOR 0.06, 95% CI 0.02-0.19) degree of interactional justice, and high degree of distributive justice (AOR 0.37, 95% CI 0.18-0.76) were significantly associated with workplace bullying among junior doctors. Discussion and Conclusion: The systematic review indicated that junior doctors worldwide commonly experience workplace bullying, which is multi-causal and linked to ill health and adverse work outcomes. Correspondingly, the present study demonstrated that workplace bullying is a significant issue for Malaysian junior doctors, and is related to both individual traits and organisational characteristics. Targeted policy recommendations to manage workplace bullying among junior doctors include primary interventions such as education, anti-bullying policy, cognitive training, and measures to improve workplace aspects, secondary interventions such as resource-enhancement vi building, conflict management skills training, and conflict mediators, and tertiary interventions such as counselling.